A Non-Canonical Role for IRE1α Links ER and Mitochondria as Key Regulators of Astrocyte Dysfunction: Implications in Methamphetamine use and HIV-Associated Neurocognitive Disorders - Proulx, Jessica; Stacy, Satomi; Park, In-Woo; Borgmann, Kathleen (Frontiers in Neuroscience, 2022)
Astrocytes are one of the most numerous glial cells in the central nervous system (CNS) and provide essential support to neurons to ensure CNS health and function. During a neuropathological challenge, such as during human immunodeficiency virus (HIV)-1 infection or (METH)amphetamine exposure, astrocytes shift their neuroprotective functions and can become neurotoxic. Identifying cellular and molecular mechanisms underlying astrocyte dysfunction are of heightened importance to optimize the coupling between astrocytes and neurons and ensure neuronal fitness against CNS pathology, including HIV-1-associated neurocognitive disorders (HAND) and METH use disorder. Mitochondria are essential organelles for regulating metabolic, antioxidant, and inflammatory profiles. Moreover, endoplasmic reticulum (ER)-associated signaling pathways, such as calcium and the unfolded protein response (UPR), are important messengers for cellular fate and function, including inflammation and mitochondrial homeostasis. Increasing evidence supports that the three arms of the UPR are involved in the direct contact and communication between ER and mitochondria through mitochondria-associated ER membranes (MAMs). The current study investigated the effects of HIV-1 infection and chronic METH exposure on astrocyte ER and mitochondrial homeostasis and then examined the three UPR messengers as potential regulators of astrocyte mitochondrial dysfunction. Using primary human astrocytes infected with pseudotyped HIV-1 or exposed to low doses of METH for 7 days, astrocytes had increased mitochondrial oxygen consumption rate (OCR), cytosolic calcium flux and protein expression of UPR mediators. Notably, inositol-requiring protein 1α (IRE1α) was most prominently upregulated following both HIV-1 infection and chronic METH exposure. Moreover, pharmacological inhibition of the three UPR arms highlighted IRE1α as a key regulator of astrocyte metabolic function. To further explore the regulatory role of astrocyte IRE1α, astrocytes were transfected with an IRE1α overexpression vector followed by activation with the proinflammatory cytokine interleukin 1β. Overall, our findings confirm IRE1α modulates astrocyte mitochondrial respiration, glycolytic function, morphological activation, inflammation, and glutamate uptake, highlighting a novel potential target for regulating astrocyte dysfunction. Finally, these findings suggest both canonical and non-canonical UPR mechanisms of astrocyte IRE1α. Thus, additional studies are needed to determine how to best balance astrocyte IRE1α functions to both promote astrocyte neuroprotective properties while preventing neurotoxic properties during CNS pathologies.